AFLP assessment of the genetic relationships among 12 Thymus taxa occurring in Portugal. Issue 1 (27th July 2015) - da Silva, David V.; Duarte, João M.; Miguel, Maria G.; Leitão, José M.
Abstract : Thymus is a widely distributed genus in the Mediterranean region with several species endemic to the Iberian Peninsula. The genetic relationships among the 12 major Thymus taxa, T. albicans, T. caespititius, T. camphoratus, T. capitellatus, T. carnosus, T. lotocephalus, T. mastichina L. ssp. mastichina, T. pulegioides, T. villosus ssp. lusitanicus, T. villosus ssp. villosus, T. zygis ssp. sylvestris and T. zygis ssp. zygis, which occur in Portugal were assessed by AFLP (Amplified Fragment Length Polymorphisms) markers. A general agreement was found between the genetic relationships estimated by the AFLP markers and the accepted Thymus taxonomy based on morphological traits and essential oil content. The AFLP markers also supported suggestions for refinement of the taxonomy of this genus.